2020
DOI: 10.1016/j.compstruct.2019.111760
|View full text |Cite
|
Sign up to set email alerts
|

New model for the prediction of the machining depth during milling of 3D woven composite using abrasive waterjet process

Abstract: The goal is to study the influence of abrasive water jet (AWJ) machining parameters (jet pressure, traverse speed and scan step) on the cutting depth of 3D woven Carbon Fibres Reinforced Polymer (CFRP) composite. The original material linked to this non-conventional milling process has not been treated yet. The depths of cut were measured and characterized as a function of the machining parameters. Finally, two prediction models for the cutting depth are proposed and validated experimentally. An increase in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 28 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…As was aforementioned, the first model is based on the concept of elementary passes and kerf superposition, emphasizing the geometric representation of the pocket [21]. In this model, a Gaussian shaped curve is assumed to represent the incision profile of the kerf produced by a single straight pass of the jet, and then the elementary passes that are overlapped in the lateral direction are summed, creating the final shape of the cross-section of the pocket [21,33]. Although various authors consider different number of parameters for this model, in the present work, the term before the exponential (termed A) and another term in the exponential expression (termed B) are only considered for the sake of simplicity.…”
Section: First Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As was aforementioned, the first model is based on the concept of elementary passes and kerf superposition, emphasizing the geometric representation of the pocket [21]. In this model, a Gaussian shaped curve is assumed to represent the incision profile of the kerf produced by a single straight pass of the jet, and then the elementary passes that are overlapped in the lateral direction are summed, creating the final shape of the cross-section of the pocket [21,33]. Although various authors consider different number of parameters for this model, in the present work, the term before the exponential (termed A) and another term in the exponential expression (termed B) are only considered for the sake of simplicity.…”
Section: First Modelmentioning
confidence: 99%
“…This model was also later successfully employed in challenging cases in order to determine the appropriate strategy for machining corners of the pockets [31] or to identify abrasion and erosion mechanisms [32]. Finally, Sourd et al [33] compared the use of a Gaussian model of elementary passes and a power law model during both slot and pocket milling of composite materials by AWJ. It was shown that the former helped the procedure of identification of erosion regimes and an appropriate correction was applied in order to improve its limitations in some cases and achieve sufficient accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have proposed analytical models for the prediction of the milled pocket depth when machining composite materials and titanium alloys material [26,27]. In fact, the model proposed here for milling IN718 in function of the process parameters of the AWJ (pressure, traverse speed and step-over distance), is based on the equation ( 1) from previous literature work [26] related to the machining of composite materials or titanium alloys.…”
Section: Model For the Prediction Of The Depth Of Cutmentioning
confidence: 99%
“…In case of drilling, the laminate of the bottom surface was subjected to bending force; therefore, chips were generated. Sourd et al proposed two models of the depth of cut in AWJ milling of CFRPs by using pocket depth measurements and the algebraic sum of elementary passes [120].…”
Section: Mechanistic Modelmentioning
confidence: 99%